Reconstruction of Multiple Renal Arteries in Live Donor Kidney Transplantation: Moewardi Hospital Experience - Muhammad Hilmy Labibi; Syaeful Agung Wibowo; Ali Husein; Wibisono; Bimanggono Hernowo Murti; Suharto Wijanarko; Setya Anton Tusarawardaya; Arry Rodjani; Nur Rasyid; Agung Susanto; Prasetyo Sarwono Putro (Fakultas Kedokteran, Universitas Sebelas Maret, 2025)
Background: Kidney transplant is the procedure for end stage renal disease (ESRD). This treatment has longer survival advantage than dialysis. Anatomical variations in the renal vasculature like multiple renal arteries, may increase surgical difficulties and influence postoperative outcomes. Case Presentation: We report a 46-year-old female living donor with two renal arteries on the left side of kidney. The recipient was her 25-year-old daughter with end stage renal disease due to systemic lupus erythematosus. A left open donor nephrectomy was completed without complications. The two renal graft arteries were side-to-side anastomosed each other, then an end-to-side anastomosis to the external iliac artery. The kidney achieved rapid reperfusion and returned to function immediately. Doppler ultrasound examination showed the normal perfusion. The creatinine level was 1.2 mg/dL on second day postoperative and stable at 0.8 mg/dL during a three-month follow-up. Conclusion: This case highlights the feasibility of transplanting a kidney from a donor with multiple renal arteries, emphasizing the critical role of comprehensive preoperative evaluation and meticulous surgical planning in achieving optimal outcomes.